2021
DOI: 10.1002/adma.202101323
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Noncollinear Spin Textures in Thin Films of a D2d Heusler Compound

Abstract: Magnetic nano‐objects, namely antiskyrmions and Bloch skyrmions, have been found to coexist in single‐crystalline lamellae formed from bulk crystals of inverse tetragonal Heusler compounds with D2d symmetry. Here evidence is shown for magnetic nano‐objects in epitaxial thin films of Mn2RhSn formed by magnetron sputtering. These nano‐objects exhibit a wide range of sizes with stability with respect to magnetic field and temperature that is similar to single‐crystalline lamellae. However, the nano‐objects do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…For translational motion to occur, however, a depinning threshold current density must be reached, below which the electric current and pinning potential tug at the skyrmion, deforming its shape. The resulting elliptically shaped skyrmions are similar to those seen in systems with anisotropic DMI ( 28 33 ). This elliptical deformation, depicted in Fig.…”
supporting
confidence: 62%
“…For translational motion to occur, however, a depinning threshold current density must be reached, below which the electric current and pinning potential tug at the skyrmion, deforming its shape. The resulting elliptically shaped skyrmions are similar to those seen in systems with anisotropic DMI ( 28 33 ). This elliptical deformation, depicted in Fig.…”
supporting
confidence: 62%
“…We anticipate that our work will stimulate further experimental and theoretical investigations of anomalous electrical, as well as thermal transport properties of the MnPtGa system, but not limited to it. We foresee that Heusler and half-Heusler compounds, with noncollinear magnetic groundstates, [28,43,[45][46][47][48][49][50] should exhibit rich transport properties endowed by their Berry curvature, whose various manifestations remain partially unexplored and origin(s) in part unexplained. Beyond the celebrated electrodynamics of magnetic skyrmion quasi-particles, [51] Heusler compounds offer a rich platform for the exploration of their prospective use in functional spintronics devices with PMA (e.g., for SO-torque-induced switching of magnetic random access memory devices [52,53] ), with the additional motivation of establishing new transport signatures [54,55] and overall new understandings of noncollinear magnetic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Garanin et al 59 showed that it is theoretically possible for a MFM tip to write the isotropic skyrmion from the uniform ferromagnetic state in non-chiral thin films. Recently, Sharma et al 60 have found that a collection of nano-objects can be written from a thin film with the D 2d symmetry in Mn 2 RhSn in the absence of the external field. Here, we show from numerical experiments that use the material parameters of Mn 1.4 Pt 0.9 Pd 0.1 Sn which are extracted from 1 that an isolated elliptical skyrmion can be nucleated from the stripe domain state or labyrinth domain state by an MFM tip in a systematic way for the system consisting of at least a few atomic layers.…”
Section: Introductionmentioning
confidence: 99%